2010
DOI: 10.1001/archsurg.2009.229
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Liver Resection for Malignant and Benign Lesions

Abstract: In experienced hands, laparoscopic liver resection is a favorable alternative to open resection. Perioperative morbidity and mortality and long-term survival after laparoscopic resection of colorectal metastases appear to be comparable to those after open resections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 42 publications
(49 reference statements)
5
70
0
1
Order By: Relevance
“…Rövidítések ALPPS = (associating liver partition and portal pein ligation for staged hepatectomy) a májfelosztás és a májkapuvéna-lekötés összekapcsolása a szakaszos májeltávolításban; HALS = (handassisted laparoscopic surgery) kézzel asszisztált laparoszkópos sebészet A laparoszkópos sebészet kezdeti időszakából, az 1990-es évekből is vannak már irodalmi hivatkozások a máj minimálisan invazív reszekciójáról, mégis az utóbbi évti-zedben kezdődött a laparoszkópia térnyerése a májsebé-szetben [1][2][3][4]. Magyarországon is vannak már hazai betegek adatait feldolgozó közlések, de ezek jóindulatú ESETISMERTETÉS elváltozások laparoszkópos reszekciójáról számolnak be [5,6].…”
unclassified
“…Rövidítések ALPPS = (associating liver partition and portal pein ligation for staged hepatectomy) a májfelosztás és a májkapuvéna-lekötés összekapcsolása a szakaszos májeltávolításban; HALS = (handassisted laparoscopic surgery) kézzel asszisztált laparoszkópos sebészet A laparoszkópos sebészet kezdeti időszakából, az 1990-es évekből is vannak már irodalmi hivatkozások a máj minimálisan invazív reszekciójáról, mégis az utóbbi évti-zedben kezdődött a laparoszkópia térnyerése a májsebé-szetben [1][2][3][4]. Magyarországon is vannak már hazai betegek adatait feldolgozó közlések, de ezek jóindulatú ESETISMERTETÉS elváltozások laparoszkópos reszekciójáról számolnak be [5,6].…”
unclassified
“…[2][3][4][5][6] While early experience was focused on benign diagnoses, this approach is now used for many hepatic malignancies. [7][8][9][10][11] It is accepted that minimally invasive liver resections have similar perioperative morbidity, mortality and long-term survival as open resections, 5,9 and some studies have shown that laparoscopic liver resection is associated with less blood loss, shorter hospital stay and comparable longterm survival. 12 However, the procedures are technically demand ing, and advanced skills in laparoscopy are required.…”
mentioning
confidence: 99%
“…[36] The percentages of liver resections performed laparoscopically now range from 25% to 65% in highvolume expert centres such as University Hospital Southampton NHS (Southampton, UK), Henri Mondor (Paris, France), UPMC (Pittsburgh, USA), UZ Leuven (Leuven, Belgium) and Rikshospitalet (Oslo, Norway). [36,63] Although it is to be expected that many centres worldwide will adopt laparoscopic liver resection as a more or less standard procedure in the near future, there are still many patients and surgeons that prefer the open procedure long beyond the learning curve. In parallel with the development of laparoscopic liver surgery, 'fast-track' programmes in various areas of surgery, including liver surgery, are gaining popularity.…”
Section: Discussionmentioning
confidence: 99%
“…Operative techniques, chemotherapy and perioperative care have evolved and have resulted in post-operative mortality rates of <5%, morbidity rates ranging between 30% and 50% [54][55][56][57], and with 5-year survival rates of approximately 30-60%. [57][58][59][60][61][62][63] The "cure" rate based on actual 10-year survivors is around 25-35%. [57,63,64] While the first limited laparoscopic liver resection in the Netherlands was performed in 1995, the first laparoscopic liver resections had already been performed 5 years earlier by Reich [65] and Gagner.…”
Section: Open Vs Laparoscopic Hepatectomymentioning
confidence: 99%
See 1 more Smart Citation